2016
DOI: 10.1037/edu0000058
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation-based disparities in school and juvenile justice discipline: A multiple group comparison of contributing factors.

Abstract: There is little data on whether school discipline or juvenile justice sanctions are directed disproportionately toward sexual minority youth (e.g., lesbian, gay, bisexual, or questioning; LGBQ) compared with heterosexual youth and even less on factors that may relate to such disparities. We tested for sexual orientation-based disparities in school suspension and juvenile justice system involvement, and tested a model linking students' sexual orientation to victimization, punishable infractions (substance use, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 69 publications
(146 reference statements)
5
59
0
Order By: Relevance
“…Using teacher- and student-level data from 745 California schools, they documented support for both cases. These findings add to the literature that also indicates that LGBTQ students face disproportionately higher rates of punitive discipline than their heterosexual peers and that this may be due to bias (Himmelstein & Brückner, 2011; Palmer, Greytak, & Kosciw, 2016; Poteat, Scheer, & Chong, 2016; Snapp, Hoenig, Fields, & Russell, 2015). Thus, the findings point to additional concerns underlying the use of highly punitive and exclusionary discipline over more constructive and holistic forms of intervention.…”
Section: Introduction To the Special Sectionsupporting
confidence: 62%
“…Using teacher- and student-level data from 745 California schools, they documented support for both cases. These findings add to the literature that also indicates that LGBTQ students face disproportionately higher rates of punitive discipline than their heterosexual peers and that this may be due to bias (Himmelstein & Brückner, 2011; Palmer, Greytak, & Kosciw, 2016; Poteat, Scheer, & Chong, 2016; Snapp, Hoenig, Fields, & Russell, 2015). Thus, the findings point to additional concerns underlying the use of highly punitive and exclusionary discipline over more constructive and holistic forms of intervention.…”
Section: Introduction To the Special Sectionsupporting
confidence: 62%
“…Interestingly, sexual minority respondents were not more likely to report higher rates of school expulsion than their heterosexual peers (ibid). However, a more recent cross-sectional analysis of the Dane County Youth Survey (Wisconsin) found that LGBQ youth were more likely to report school suspensions, as well as juvenile justice system involvement (Poteat, Scheer & Chong 2016). In both studies, the differences in criminal sanctioning were particularly disparate between sexual minority and majority girls, and these differences were not sufficiently explained by differences in behavior.…”
Section: Introductionmentioning
confidence: 99%
“…LGBT youth are overrepresented in the justice system as well, making up 20% of all juveniles; among these, 85% are Youth of Color (Center for American Progress, 2016). In one study, sexual minority youth reported experiencing harsher school discipline, and being more involved in the justice system, than their nonsexual minority peers (Poteat, Scheer, & Chong, 2016). In a study of 55 LGBT youth involved with the justice system, over 90% of participants reported problems related to lack of parental support (Majd, Marksamer, & Reyes, 2009).…”
Section: Justice-involved Youthmentioning
confidence: 99%